Analisis Penentuan Kandungan Gas Oksigen (O2) Fotosintesis Tanaman Gelombang Cinta (Anthuriumsp) Pada Variasi Daya Lampu - RR Ersi Nurmaeli; Moh. Taifur (Universitas Sarjanawiyata Tamansiswa, 2015)
Fotositesis research has been done using a light source at the plant by analyzing the oxygen gas is produced. This study aims to determine the effective power light on the photosynthesis of plants. Gas levels of oxygen as a result of photosynthesis can be seen by using a tool-assisted oxygen sensor logger software pro.Plant sample used was a wave of love (Anthurium sp), aged approximately 5 months the number of leaves 4-5 pieces inserted in a tube or jar is closed. Variations lamp power used is 33 watts, 60 watts and 100 watts. Data were collected for 600 seconds for each lamp power. The resulting oxygen levels on photosynthesis recorded using Pro logger software then exported to Microsoft Excel for graphed. The curve is formed can be used to analyze the relationship between oxygen levels with time at each power lights are used. After curve fitting the data to form done by creating a line equation and R2 to analyze the most effective lamp power to increase the rate of photosynthesis.In this study showed that the greater the power of the lamp, the oxygen levels increased. Increased levels of oxygen means that the amount of oxygen produced during photosynthesis is greater than the amount of oxygen used for respiration. From the comparison of the three lights that have different power and graphed equation of the line, turns on the use lamps with power 66 watt and 100 watt having the largest gradient is 0.001. Mean increase in oxygen levels on both the power of this light is very large, while the gradient equation of a line on the lights with 33 watt power is the same, namely 0.0001. Comparison between the use of power 66 watt lamp has a gradient of 0.001, while the 100-watt power gradient 0.0011 has so increased oxygen levels is the most effective at 100 watts of power. R2 at 66 watts power is 100 watts of power 0.9535 while 0.9899. The conclusion for this study were 1) the greater power of the lights then the higher the rate of photosynthesis, and effective lamp power is 100 watts.